A dimensão autoetnográfica do Projeto Dicionários de Artista - Lança, Filipa Pontes, 1978- (2018)
"ArtistDictionaries: The experience of the place. Autoethnography in the field of Drawing "is an ongoing art based research, with focus on the relations and intersections between autoethnographic processes and the practice of contemporary drawing. It proposes to discuss 'autoethnographic drawing' as a field of production and research, problematizing the terrain of appropriations between artistic practice and ethnographic experience, from an artistic perspective. Taking the contemporary drawing, site-specific, and autoethnography as key concepts, the present communication focuses on the presentation and argumentation of the autoethnographic dimension of the ArtistDictionaries project (which is the starting point of the PhD program) to share a set of references, foundations and experiences that are being developed within the research